2015
DOI: 10.1371/journal.pone.0125672
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiling in Clear Cell Renal Cell Carcinoma: Identification and Functional Validation of Key miRNAs

Abstract: ObjectiveThis study aims to profile dysregulated microRNA (miRNA) expression in clear cell renal cell carcinoma (ccRCC) and to identify key regulatory miRNAs in ccRCC.Methods and ResultsmiRNA expression profiles in nine pairs of ccRCC tumor samples at three different stages and the adjacent, non-tumorous tissues were investigated using miRNA arrays. Eleven miRNAs were identified to be commonly dysregulated, including three up-regulated (miR-487a, miR-491-3p and miR-452) and eight down-regulated (miR-125b, miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…52,53 miRNA expression signatures of RCC We also reviewed six recently published miRNA expression signatures comparing RCC and normal kidney tissue using clinical specimens (Table 3). [18][19][20][21][22][23] Two signatures were constructed from deep sequencing and the other four signatures were constructed from microarrays. Commonly downregulated miRNAs or upregulated miRNAs in multiple signatures are listed in Table 4, sorted according to the number of signatures.…”
Section: Downregulated Mirnas In Multiple Bc Signaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…52,53 miRNA expression signatures of RCC We also reviewed six recently published miRNA expression signatures comparing RCC and normal kidney tissue using clinical specimens (Table 3). [18][19][20][21][22][23] Two signatures were constructed from deep sequencing and the other four signatures were constructed from microarrays. Commonly downregulated miRNAs or upregulated miRNAs in multiple signatures are listed in Table 4, sorted according to the number of signatures.…”
Section: Downregulated Mirnas In Multiple Bc Signaturesmentioning
confidence: 99%
“…In this review, we summarize aberrantly expressed miRNAs based on current BC and RCC miRNA signatures. [11][12][13][14][15][16][17][18][19][20][21][22][23] We discuss the dysregulated expression of the miR-200 family and miR-200 family target genes in BC and RCC.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of miR-125b has been revealed to be deregulated in a number of types of cancer, including gastric cancer (16), non-small-cell lung cancer (NSCLC) (19) and osteosarcoma (12). Numerous previous studies about gene microarray in RCC revealed that miR-125b was downregulated in ccRCC tissues (20)(21)(22). However, another study identified that miR-125b was upregulated in ccRCC by performing ISH (17).…”
Section: Discussionmentioning
confidence: 99%
“…miR-22 was found down-regulated in clear cell renal cell carcinoma (RCR) samples when compared to adjacent non-tumorous samples (He et al , 2015). The expression of miR-128 was reported also as down-regulated in the kidneys of patients with progressive versus stable chronic kidney disease (Rudnicki et al , 2016).…”
Section: Discussionmentioning
confidence: 99%